TEMPORAL BEHAVIOR OF MARINE LANDINGS ALONG COASTAL KARNATAKA.I.RELATIVE DISTRIBUTION AND SECULAR TRENDS - GADAGKAR, SUDHINDRA R; SUNDARARAJ, N (Fishery Technology, 2017)
Landing data of 21 fisheries from Karnataka (quarterly landings for the period 1956 to 1978 and annual landings for the period 1979 to 1981) were analysed to study the te111poral behaviour of the landings. The relative distribution and secular trends in each of the fisheries are reported. On an average, mackerel and oil sardine together account for about 70% of the annual landings. The fluctuation in the landings in all the fisheries w2s very high with the coefficient of variation attaining a minimum value of 61.53%. The inverse relationship tetwee:n the landings of oil sardine and mackerel was found to be statiE:tically significant.It is suggested that fishing effort be further increased in fisheries that have demonstrated a rising trend (about 73% of the total annual landings) as also in the case of the fisheries whose trends appear stagnant (about 21;6 of the annual landings). However, there seems to be some evidence of a need for regulating fishing in Hemirhamphus and Belone, Caranx and penaeid prawns. Regulations need to be made authentic with the help of sufficient information on not merely the fishery but on the whole population.